2021
DOI: 10.3892/or.2021.7962
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin promotes cell cycle arrest and apoptosis of acute myeloid leukemia cells by inactivating AKT

Abstract: Curcumin, a phytochemical from rhizomes of the plant Curcuma longa , has been reported to exert potential anticancer properties in various cancer types, including acute myeloid leukemia (AML). However, the underlying mechanism remains poorly understood. The present study demonstrated that curcumin had a stronger cytotoxic activity against AML cells compared with three other types of phytochemicals (epigallocatechin gallate, genistein and resveratrol). Protein phosphorylation profiling us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 31 publications
2
17
0
Order By: Relevance
“…This computational efficacy was undoubtedly translated in our in vitro findings, exhibiting the dose-dependent inhibition of Akt phosphorylation by SBL-060 in both AML cell types. Previous studies have shown that cell cycle alterations and apoptosis induction can occur by inhibiting Akt kinase in AML cells [27][28][29]. The results of the present study corroborate those of previous reports, suggesting the efficacy of SBL-060 against AML cells by inhibiting Akt, thus hindering the regular cell cycle and inducing cellular apoptosis.…”
Section: Discussionsupporting
confidence: 91%
“…This computational efficacy was undoubtedly translated in our in vitro findings, exhibiting the dose-dependent inhibition of Akt phosphorylation by SBL-060 in both AML cell types. Previous studies have shown that cell cycle alterations and apoptosis induction can occur by inhibiting Akt kinase in AML cells [27][28][29]. The results of the present study corroborate those of previous reports, suggesting the efficacy of SBL-060 against AML cells by inhibiting Akt, thus hindering the regular cell cycle and inducing cellular apoptosis.…”
Section: Discussionsupporting
confidence: 91%
“…Based on the cell viability assay, we wondered whether high Cur dosages induced a proliferation arrest or cell death. It is known that Cur can elicit different effects on several cellular processes such as cell death, inflammation, oxidative stress, angiogenesis, and autophagy, depending on the dose administered [ 6 , 8 , 9 , 12 , 21 , 22 , 23 , 24 , 25 , 26 ]. Hence, we used flow cytometry for the analysis in apoptosis levels.…”
Section: Resultsmentioning
confidence: 99%
“…The sequence of siTsc1: GCUUUGACUCUCCCUUCUA [ 15 ]. SC-79 (10 ÎŒM; MCE, Shanghai, China) was used to treat PASMCs for 24 h [ 16 ].…”
Section: Methodsmentioning
confidence: 99%